Relationship Between Parental Patterns and Stunting Incidence in Toddlers Aged 12-24 Months in the Biloro Public Health Center Areas, South Buru District - Supriyanto, Supriyanto; Waliulu, Syariefah H (UNIMUS Web Conferences, 2026)
Background: Stunting is a chronic nutritional problem that affects a child’s physical growth and cognitive development, and increases the risk of non-communicable diseases in adulthood. One of the influencing factors of stunting is parenting style. Buru Selatan Regency continues to record a high prevalence of stunting, especially in the working area of Biloro Health Center. Objective: This study aims to determine the relationship between parenting style and the incidence of stunting among children aged 12–24 months in the working area of the Biloro Health Center, Buru Selatan Regency. Method: This research employed a correlational analytic design with a cross-sectional approach. A total of 71 mothers with children aged 12–24 months were selected using a random sampling technique. Data were collected using a parenting style questionnaire and direct anthropometric observations of children’s height-for-age (H/A) using the Z-score. Data were analyzed using the chi-square test with a significance level of 0.05. Results: Most respondents applied a democratic parenting style (69%), while 50.7% of children were found to be stunted. The analysis showed a significant relationship between parenting style and stunting incidence (p-value < 0.05. Discussion: Democratic parenting is beneficial, families with low economic status may struggle to provide a balanced, nutritious diet for their children. Conclusion: There is a significant relationship between parenting style and stunting in children. Inappropriate parenting practices may increase the risk of stunting. Educational interventions related to parenting and child nutrition are essential to reduce stunting cases.